Reliability and concurrent validity of the iHandy level mobile application to measure thoracolumbar range of motion in low back pain patients - Nimra Ijaz; Saima Riaz; Tahreem Raza; Sidra Ali (Physiotherapy Quarterly)
Introduction The use of smartphone technology and software (apps), in addition to an inclinometer and goniometer, has expanded the clinician’s assessment possibilities. However, the legitimacy and trustworthiness of these cell phones and applications are still questioned. This study aimed to determine the reliability and concurrent validity of the iHandy level mobile application to measure the thoracolumbar range of motion in people with low back pain.